The flowers in your dustbin: Girls in the North American punk subcultures of the 1990s - Leblanc, Lauraine (Université Emory, 1997)
Girls in male-dominated youth subcultures confront ideologies of gender which remain largely invisible and often tacitly accepted in many women's everyday lives. Punk girls choose to construct their femininity within a highly male-dominated, "masculinist," context; girls are present in such youth subcultures, but the masculine definition of their norms problematizes their participation. Thus, punk girls struggle to accommodate female gender norms within subcultural identities which are deliberately coded as "masculine." Although young women in America encounter the norms of the female gender role on a daily basis, punk girls' negotiations between the norms of femininity and those of punk open these prescriptions to critical examination which they might not otherwise be accorded. In this dissertation, I explore accounts of punk girls' engagements with both mainstream and subcultural gender norms. In constructing this account of girls' lived experiences in the punk subculture, I rely primarily upon the phenomenology, or experiential narrative, of punk girls' everyday lives. I elicited these accounts within the context of conducting participant observation m the punk scenes of four North American cities (Atlanta, Montreal, New Orleans, and San Francisco) from 1993 to 1995, conducting ethnographic interviews with forty punk girls. In the following, I explore various facets of punk girls' engagements with gender norms, including punk girls' narratives of engagement with the subculture; the construction of punk as a discourse of masculinity; punk girls' stylistic, behavioral, and discursive reconstructions of femininity; punk girls' experiences of public harassment and sexual harassment, and their strategic responses to these. I argue that these girls use the punk subculture in order to carry out resistances to varied forms of gender oppression, thereby developing stronger self-concepts in the face of adversity.

La chanson sentimentale dans la culture populaire : le cas Michel Louvain - Savoie, Chantal (Université du Québec à Montréal, 1995)

La turlute amoureuse. Érotisme et chanson traditionnelle - Julien, Jacques (Éditions Triptyque, 1990)
La tryannie des censeurs a étouffé la chanson traditionnelle sous les voiles de la moralité. Si elle ne peut renaître vive et provoquante dans les parcs des cités, qu'on lui arrache au moins ces suaires. Parodiant ces vierges imputrescibles que la dévotion vénère, on verra que la brunette chanson porte encore un sourire qui gagne jusqu'à la fossette du menton. Encore un peu qu'elle siffflerait son âne pour répondre à la'ppel de la cornemuse.

Les représentations des rapports hommes-femmes dans la chanson populaire au Québec - Nadeau, Sylvie (Université Laval, 1987)

The Relationship of Physical and Spiritual Love in the Work of Leonard Cohen - Thompson, Harrell Jerome (Université Texas Tech, 1972)